2002
DOI: 10.1093/emboj/cdf678
|View full text |Cite
|
Sign up to set email alerts
|

Human Dcp2: a catalytically active mRNA decapping enzyme located in specific cytoplasmic structures

Abstract: We have cloned cDNAs for the human homologues of the yeast Dcp1 and Dcp2 factors involved in the major (5¢±3¢) and NMD mRNA decay pathways. While yeast Dcp1 has been reported to be the decapping enzyme, we show that recombinant human Dcp2 (hDcp2) is enzymatically active. Dcp2 activity appears evolutionarily conserved. Mutational and biochemical analyses indicate that the hDcp2 MutT/Nudix domain mediates this activity. hDcp2 generates m7GDP and 5¢-phosphorylated mRNAs that are 5¢±3¢ exonuclease substrates. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
442
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(465 citation statements)
references
References 37 publications
19
442
0
4
Order By: Relevance
“…GWB are named from the marker protein GW182, which contains multiple glycine (G) and tryptophan (W) repeats and a classic RNA binding domain at the carboxyl terminus (Eystathioy et al, 2002a). The mRNA decay factors/complexes found in GWB include the deadenylase Ccr4, the decapping complex Dcp1a/1b/Dcp2, the LSm1-7 complex, Ge-1 (also known as Hedls), rck/p54, and exonuclease Xrn1 (Bashkirov et al, 1997;van Dijk et al, 2002;Ingelfinger et al, 2002;Lykke-Andersen, 2002;Eystathioy et al, 2003;Cougot et al, 2004;Andrei et al, 2005;Yu et al, 2005;Fenger-Gron et al, 2005). GWB are physically juxtaposed to and transiently interact with stress granules (SG).…”
Section: Introductionmentioning
confidence: 99%
“…GWB are named from the marker protein GW182, which contains multiple glycine (G) and tryptophan (W) repeats and a classic RNA binding domain at the carboxyl terminus (Eystathioy et al, 2002a). The mRNA decay factors/complexes found in GWB include the deadenylase Ccr4, the decapping complex Dcp1a/1b/Dcp2, the LSm1-7 complex, Ge-1 (also known as Hedls), rck/p54, and exonuclease Xrn1 (Bashkirov et al, 1997;van Dijk et al, 2002;Ingelfinger et al, 2002;Lykke-Andersen, 2002;Eystathioy et al, 2003;Cougot et al, 2004;Andrei et al, 2005;Yu et al, 2005;Fenger-Gron et al, 2005). GWB are physically juxtaposed to and transiently interact with stress granules (SG).…”
Section: Introductionmentioning
confidence: 99%
“…DNA Constructs. pNEGFP-hDCP1a (van Dijk et al, 2002;Pillai et al, 2005) was kind gift from Dr. Jens Lykke-Andersen (University of Colorado, Boulder, CO), transfected as 0.4 g/well (24-well plate).…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Quantification of siLuc and siSMN colocalization to P-bodies showed a lower but again highly significant colocalization coefficient (siLuc, 0.159 Ϯ 0.09; siSMN, 0.15 Ϯ 0.03, p Ͻ 0.01). On monitoring siRNA localization in live cells expressing the P-body decapping enzyme component hDcp1a tagged with eGFP (eGFP-hDcp1a) to visualize P-bodies (van Dijk et al, 2002;Pillai et al, 2005), we saw that siRNAs could be found in P-bodies within 30 min of transfection ( Supplemental Figure 1). Some large bodies containing intense siRNA signals were also present; these have been described previously to be vesicles/endosomes that remained from transfection (Jakymiw et al, 2005).…”
mentioning
confidence: 99%
“…In the other pathway, shortening of the poly(A) tail leads to the removal of the cap structure of the mRNA by the decapping proteins DCP1 and DCP2 facilitating 5Ј-3Ј degradation of the mRNA through the exoribonuclease XRN1 (Beelman and Parker, 1995;Butler, 2002). These proteins colocalize in discrete cytoplasmic foci in mammalian cells, termed processing bodies or P-bodies (also known as DCP1-or GW182-bodies), indicating that mRNA decay is restricted to distinct cytoplasmic compartments in mammalian cells (van Dijk et al, 2002;Cougot et al, 2004). The human protein CCR4, which is involved in mRNA deadenylation, the decapping stimulating LSm proteins LSm1-7, the DEAD/Hbox RNA helicase DDX6 (also known as RCK/p54), GW182, and Ge-1 are components of P-bodies (Bouveret et al, 2000;Eystathioy et al, 2002;Ingelfinger et al, 2002; LykkeAndersen, 2002;Cougot et al, 2004;Yu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Images were taken using Zeiss software LSM 5 version 3.5. The following antibodies were used: TIA-1 (1:100; Santa Cruz Biotechnology, Santa Cruz, CA), DDX6 (1:500; Novus Biologicals), hemagglutinin (1:500; Roche Diagnostics), FLAG (1:500; Sigma Chemie), DCP1 (1:600; van Dijk et al, 2002), PABP (1:500; (Kuyumcu-Martinez et al, 2004), ATXN2 (1:200; BD Biosciences); MYC (1:600; Upstate Biotechnology, Lake Placid, NY); ␣-goat-Cy3 or ␣-rabbit-Cy3 (1:500; Dianova, Hamburg, Germany), and ␣-mouse-fluorescein isothiocyanate (FITC) (1:500; Dianova). …”
mentioning
confidence: 99%